2017
DOI: 10.1007/s10803-017-3242-x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Psychometric Evaluation of the Autism Stigma and Knowledge Questionnaire (ASK-Q)

Abstract: ASD knowledge deficits contribute to disparities in the timing and quality of ASD services. To address the limitations with existing measures of ASD knowledge, we developed and examined the Autism Stigma and Knowledge Questionnaire (ASK-Q), which comprehensively assesses multiple subdomains of ASD knowledge while maintaining strong psychometric support and cross-cultural utility. ASK-Q items derived from the published research are organized into four subscales: (i) diagnosis, (ii) etiology, (iii) treatment, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 49 publications
0
87
1
2
Order By: Relevance
“…Overall, the instrument used in this study, specifically the ASD Beliefs Questionnaire (ABQ), consisted of two sections. The items in the developed instrument were adapted from questionnaires by Harrison et al [ 58 ] and Al-Sharbati et al [ 59 ], with their permission. The first section focused on the demographic information of the respondents (i.e., gender, age, marital status, education level, and teaching experience).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, the instrument used in this study, specifically the ASD Beliefs Questionnaire (ABQ), consisted of two sections. The items in the developed instrument were adapted from questionnaires by Harrison et al [ 58 ] and Al-Sharbati et al [ 59 ], with their permission. The first section focused on the demographic information of the respondents (i.e., gender, age, marital status, education level, and teaching experience).…”
Section: Methodsmentioning
confidence: 99%
“…1 That is, the attitudes of nonautistic individuals in the social environment need to be considered and adjusted to better support autistic individuals, 2,3 rather than focusing on eliminating their autistic symptoms. While previous studies have examined nonautistic individuals' openness to, 4,5 stigmatization of, 6,7 and awareness of 6 autism, this study proposes autism acceptance as a new attitude construct to be studied and measured.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the Openness Scale measures how much a person likes to be around an autistic peer or how much a person thinks an autistic peer is different from him/her. 5 Other researchers have examined stigma associated with autism, a construct likely to be inversely related to acceptance, using the Autism Stigma and Knowledge Questionnaire (ASK-Q) 7 or the Social Distance Scale. 6 These attitude scales have enabled research on factors that are potentially associated with attitudes toward autism such as previous contact experience, autism knowledge, awareness of neurodiversity framework, and various demographic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Research on stigmatizing attitudes toward mental illness held by healthcare professionals such as nurses and psychiatrists found conflicting results on the association between stigmatizing attitudes toward mental illness and demographic features such as healthcare professionals’ age (Chambers et al 2010 ; Hansson et al 2013 ; Högberg et al 2012 ; Kopera et al 2015 ; Mosaku and Wallymahmed 2016 ; Reavley et al 2014 ; Siqueira et al 2017 ; Smith and Cashwell 2010 ; Tay et al 2004 ; Vibha et al 2008 ; Winkler et al 2016 ) or work experience (Gras et al 2015 ; Mosaku and Wallymahmed 2016 ; Smith and Cashwell 2010 ). Although stigmatizing attitudes toward ASD are often implicitly imbedded in ASD knowledge questionnaires (Harrison et al 2017a ), we found no studies evaluating ASD stigma in healthcare professionals nor any literature on how stigma toward mental illness relates to stigma toward autism. Nor did we find any studies evaluating the level of stigmatizing attitudes toward mental illness in physicians who screen for health problems and developmental issues in children in the general population.…”
Section: Introductionmentioning
confidence: 78%
“…We evaluated ASD knowledge with a self-developed questionnaire as we could not identify suitable questionnaires at the start of the study. During the course of this study, the Autism Stigma and Knowledge Questionnaire (ASK-Q) was developed for evaluating both ASD knowledge and stigma and has strong psychometric properties (Harrison et al 2019 ; Harrison et al 2017a ). While the CAMI is widely used to assess stigmatizing attitudes toward mental illness in general, it is unknown how the CAMI relates to stigma toward autism.…”
Section: Discussionmentioning
confidence: 99%